Variation in policies for the management of febrile neutropenia in United Kingdom Children's Cancer Study Group centres. Issue 6 (6th February 2007) - Phillips, Bob; Selwood, Karen; Lane, Sheila M; Skinner, Roderick; Gibson, Faith; Chisholm, Julia C
Abstract : Objective: To assess the variation in the current UK management strategies for the treatment of febrile neutropenia in childhood. Design and setting: A postal survey of all 21 United Kingdom Children's Cancer Study Group (UKCCSG) centres assessing and collating local policies, protocols or guidelines relating to the management of febrile neutropenia. Further direct contact was undertaken to clarify any uncertainties. Results: All 21 centres provided information. The policies used to manage febrile neutropenia in the centres around the UK vary in almost every aspect of management. Definitions of fever ranged from a persistent temperature of >37.5°C to a single reading of >39°C. Neutropenia was inconsistently defined as an absolute neutrophil count of <1×10 9, <0.75×10 9 or <0.5×10 9 . Choices of antibiotic approaches, empirical modifications and antistaphylococcal treatment were different in each protocol. The use of risk stratification was undertaken in 11 centres, with six using a policy of reduced intensity therapy in low risk cases. Empirical antifungal treatment was very poorly described and varied even more widely. Conclusions: There was a great deal of variation in definitions and treatment of febrile neutropenia in the UKCCSG children's cancer treatment centres. A degree of variation as a result of local microbiological differences is to be expected, but beyond this we should seek to standardise the core of our approach to defining fever and neutropenia, risk stratification and duration of empirical therapy in a way that maintains safety, minimises resource utilisation and maximises quality of life.